Effects of Different Lung Lavage Solutions on Lung Injury - Hicran Gündoğdu; Perihan E. Özcan; Lütfi Telci; İ. Ozkan Akıncı (Galenos Yayinevi, 2011)
Aim: Experimental animal studies showed that lactated Ringer solution have beneficial effects over isotonic saline solution (0.9% NaCl) for mucociliar activity and clearance of upper respiratory tract. In this study we evaluated the effect of lactated Ringer solution and isotonic saline solution on rat lungs for lung injury. Material and Method: Istanbul University, Istanbul Medical Faculty, Experimental Animal Researches Study Institute ethical committee approval was obtained for 24 Sprague-Dawley rats each weighing between 250-300 g. Rats were tracheostomized under general anesthesia and ventilated using pressure controlled ventilation mode. As the first part of our study, we aimed to find the adequate lavage volume of isotonic saline and lactated Ringer solutions to induce ARDS. After finding the adequate lavage volume and count; the mean lavage count that induce ARDS, rest of the rats were randomly divided into two groups and tracheal lavages were performed according to predetermined lavage volume and count in the second part of the study. Wet/dry body weight counts, arterial blood gas sampling and microalbumin levels of bronchoalveolar lavage were analyzed for assessment of lung injury. Results: ARDS was developed following 11.4 lavages with isotonic saline solution and 10.57 lavages with lactated Ringer solutions. In the second part of the study, wet/dry body weight and BAL microalbumin levels were found lower in isotonic saline group however the difference between groups were not statistically significant. Conclusion: We were not able to demonstrate the superiority of using lactated Ringer solution over isotonic saline in terms of lung injury when used for lung lavage in rats. (Journal of the Turkish Society Intensive Care 2011; 9:48-52)